Bimbingan Konseling Islam Melalui Dakwah Mau’izah Hasanah Dalam Memperbaiki Perilaku Negatif Pada Santriwati Pondok Pesantren Daarul Hikmah - Suci Ayu Andini; Kusnadi Kusnadi; Selvia Assoboru (Social Science and Contemporary Issues Journal, 2024)
This research discusses "Islamic Counseling Guidance Through Da'wah Mau'izah Hasanah in Correcting Negative Behavior in Students of the Daarul Hikmah Islamic Boarding School, Talang Kelapa District". This research aims to increase positive behavior and find out Islamic Counseling Guidance through Mau'izah Hasanah Da'wah in Correcting Negative Behavior in Pupils at the Daarul Hikmah Islamic Boarding School, Talang Kelapa District. This type of research is a type of field research with a descriptive approach. Data collection tools include observation, interviews and documentation. Meanwhile, the data analysis techniques are data reduction, data presentation, and drawing conclusions or verification. The subjects of this research were 10 female students at the Islamic boarding school "Daarul Hikmah, Talang Kelapa District". The results of the research show that the condition of female students is better and more accepting of themselves than before. Where these female students can be seen so far being able to change themselves little by little, being more able to accept the existing situation, and continuing to try to always learn from previous situations and as time goes by and in the process of maturation they will understand and comprehend.